2017
DOI: 10.15621/ijphy/2017/v4i6/163928
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of Hand Grip Strength Measurement Using a Jamar Hand Dynamometer in Patients with Acute and Chronic Cervical Radiculopathy

Abstract: Background:To evaluate the test-retest reliability of Jamar hand held dynamometer for measuring handgrip strength (HGS) in patients with acute and chronic cervical radiculopathy and to find out the difference in measurement of the handgrip strength between acute and chronic cervical radiculopathy. Methods:A prospective, observational and non-experimental, the comparative study design was used. A sample of 72 subjects (37 women and 35 men) suffering from cervical radiculopathy were divided into two groups i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…All the three measurement tools used in the study are reliable and valid as shown by the previous studies viz, Visual Analog Scale [22]. Manual hand dynamometer [6,23,24] and DASH scale [25,26]. The handgrip strength was measured using a manual hand dynamometer three times with an interval of 60 seconds rest, and the mean score was considered as the grip strength.…”
Section: Introductionmentioning
confidence: 86%
“…All the three measurement tools used in the study are reliable and valid as shown by the previous studies viz, Visual Analog Scale [22]. Manual hand dynamometer [6,23,24] and DASH scale [25,26]. The handgrip strength was measured using a manual hand dynamometer three times with an interval of 60 seconds rest, and the mean score was considered as the grip strength.…”
Section: Introductionmentioning
confidence: 86%